Human Self-Experience in the Garden: Horticulotherapy from an Ontological-Axiological Perspective - Marlena Kilian; Michał Paluch (Studia Ecologiae et Bioethicae)
The intensively developing horticultural therapy proves the healing power of human contact with nature. This article analyses the process of self-therapy taking place in contact between a person and a garden both as its guest (passive horticultural therapy mode) and as its host (active horticultural therapy mode). It has been established that passive and active horticultural therapy includes activities involving the physical (sensations), mental (cognition), emotional (affections) and spiritual (reflections) spheres, which have been distinguished as internal human activities, while active garden therapy additionally involves the functional sphere as its external activity. Exposure to sensory stimuli initiates changes in a person’s cognitive, emotional and spiritual sensitivity, leading to self-cognition. At this stage, it is possible to switch from the identity of the visitor in the garden (performer of the action) to the identity of its host (perpetrator of the act). At this level, when creating a garden, a person experiences the values of freedom, goodness and beauty, which leads to self-transformation through self-experience. Changes taking place in a person may, in turn, translate into his horticultural activity. The ontological and axiological description proposed in the article aims to include the way of thinking derived from the Polish philosophical tradition into the international eco-pedagogical discourse.